Characterization and Depth Analysis of Organic Thin Film Transistor - Verma, Aanchal; Mittal, Poornima (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*264.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954735);" role="presentation">Organic semiconductor technology on polymer and flexible substrate is creating a base for researchers and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*277.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96092);" role="presentation">industrial communities due to their ability to find application as a low cost, flexible and large area electronic <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*290.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940732);" role="presentation">device. In this paper an overview of Organic thin film transistor (OTFT) has been done. Different structures of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9292);" role="presentation">OTFT have been explained on behalf of placement of source, gate and drain electrodes. The working principle <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965185);" role="presentation">of OTFT is enlightened with the help of energy band diagrams. As it is a three terminal device with source, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93977);" role="presentation">drain and gate electrodes the operation of OTFT is similar to that of a MOSFET with difference in the process <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992841);" role="presentation">of channel formation which is briefly described in this paper. Application of OTFT is their most attractive <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.993964);" role="presentation">feature and there are various possible ways of using it which were not possible with the silicon devices. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926354);" role="presentation">Simulation of Bottom Gate Bottom Contact (BGBC) and Bottom Gate top Contact (BGTC) OTFT structures are <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931005);" role="presentation">carried out using 2-D Simulator ATLAS by Silvaco. The results show a major difference in performance of both <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920131);" role="presentation">the structures, thus highlighting the fact that structure of OTFT plays a very important role.